Proceedings of the Thirty-First SIGCSE Technical Symposium on Computer Science Education 2000
DOI: 10.1145/330908.331875
|View full text |Cite
|
Sign up to set email alerts
|

EROSI—visualising recursion and discovering new errors

Abstract: This paper introduces a novel software visualisation aid, the EROSI (Explicit Representer Of Subprogram Invocations) tutor, hypothesised to support the acquisition (by novice programmers) of a mental model to facilitate the comprehension and use of recursion as a problem solving technique. Novices found the EROSI tutor easy to use, interesting and a valuable visualisation aid to forming correct mental models of recursive processes. Studies concluded that although novices many have a correct mental model of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The forward passing of control is called the "active flow" and the backward flow of control is called the "passive flow" [1]. Mental models of recursion describe students' understanding of recursion and a number have been discovered [4,3].…”
Section: Mental Models Of Recursionmentioning
confidence: 99%
“…The forward passing of control is called the "active flow" and the backward flow of control is called the "passive flow" [1]. Mental models of recursion describe students' understanding of recursion and a number have been discovered [4,3].…”
Section: Mental Models Of Recursionmentioning
confidence: 99%
“…Most of them are based on the "copies model" of recursion, that is, they show a different copy of either code or data for each recursive call. We may cite Recursion Animator [15], SimRECUR [16], Function Visualizer [3] and EROSI [6]. Flopex 2 [4] is an Excel extension for visual programming.…”
Section: Related Workmentioning
confidence: 99%
“…Further investigation of these subjects revealed that five of them had demonstrated a 'good understanding' of the copies execution of the similarly structured embedded recursive algorithm in Question 2, and eleven for Question 3. A 'good understanding' meant that either the question was answered correctly or the subject made a simple error (due to exogenous factors [4]) during the particular task.…”
Section: Summaw Of Findingsmentioning
confidence: 99%
“…Recursion is a powerful aroblem solving technique in programming [ 1] and therefore ~,n important area for computer science education research. George [3,4] developed the EROSI (Explicit Representer o f Subprogram Invocations) tutor to aid novices in developing the copies model o f recursion which experts possess [7]. In the copies model, recursion is defined as a process which is capable o f triggering new instantiations (or copies) o f itself with control passing forward to successive instantiations (active flow) and back to suspended ones (passive flow).…”
Section: Introductionmentioning
confidence: 99%